A numerical and experimental study of woven fabric material under ballistic impacts. (June 2016) - Fang, Hongbing; Gutowski, Matthew; DiSogra, Matthew; Wang, Qian
Highlights: Finite Element models were created for single- and multi-layer woven fabrics. Both FE models were used in simulations of ballistic impacts at various velocities. Ballistic impact tests were conducted on a woven fabric in-service groin protector. Simulations of ballistic impact tests were performed using the validated FE model. Fabric responses predicted by FE models matched reasonably well with test data. Abstract: The objective of this research was to use finite element modeling and simulations to evaluate the ballistic resistance of woven fabrics and soft body armor. In the work of this paper, nonlinear finite element (FE) simulations were performed to evaluate the response of single- and multi-layer woven fabrics under ballistic impacts. A shell-element based fabric material model was first validated using perforation tests performed on a single-layer fabric under high-velocity impact by a spherical steel projectile. The validated model was then used to replicate high- and low-velocity impacts by a blunt aluminum projectile on eight-layer Kevlar targets. Results from the multi-layer simulations were shown to have good agreement with experimental data. Finally, the validated fabric model was used to simulate a full-scale ballistic test on a groin protector panel of the interceptor body armor system. The simulation results of both the single- and multi-layer impacts were shown to match well with experimental data in terms of the projectile's residual velocities. This research confirms the effectiveness of the fabric model and can be extended to a wide range of applications involving soft body armors.